Respuestas

2013-06-05T20:00:51+02:00
Tipo A - A^2 + 2Ab + B^2
tipo B - A^2 - 2AB + B^2
tipo C - A^2 - B^2
2013-06-05T23:24:06+02:00
Binomio al cuadrado

(a ± b)2 = a2 ± 2 · a · b + b2

(x + 3)2 = x 2 + 2 · x ·3 + 32 = x 2 + 6 x + 9(2x − 3)2 = (2x)2 − 2 · 2x · 3 + 32 = 4x2 − 12 x + 9

Suma por diferencia

(a + b) · (a − b) = a2 − b2
(2x + 5) · (2x - 5) = (2x)2 − 52 = 4x2 − 25

Binomio al cubo

(a ± b)3 = a3 ± 3 · a2 · b + 3 · a · b2 ± b3

(x + 3)3 = x3 + 3 · x2 · 3 + 3 · x · 3+ 33 =
x 3 + 9x2 + 27x + 27(2x − 3)3 = (2x)3 − 3 · (2x)2 ·3 + 3 · 2x · 32 − 33 = 8x 3 − 36x2 + 54x − 27